Religious Mediation, Sensational Forms, and Counter-Counterpublics: Films By and For Orthodox Jewish Women Only - Rothenberg, Celia E. (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2023)
This paper examines the genre of films being produced by Orthodox Jewish women and intended to be viewed only by other women [i.e., Orthodox Jewish women] as a key form of “sensational" religious materiality and a counter-counterpublic sphere of religious action. Religious materiality is all that makes religious sentiment, knowledge, and practice knowable; it is the “stuff” of religious life and belief. These films present “sensational forms” of religious materiality, or, in other words, experiences that “induce religious modes of sensing, feeling, and making sense that effect the very ‘beyond’ that is posited and form the people addressed as believers” to audiences (Meyer 2015). Focusing on religious films as a key form of and forum for sensational religious materiality moves away from not only a Protestant-style bias focused on the role of interior belief and disregard for “entertainment” media, but also a simple “religion and [+] media” instrumentalist approach. Further, films produced by and for Orthodox Jewish women, while broadly part of the religious counterpublic media of Orthodox Jewry, are further located in a gendered location; the films are thus productively described as located in a counter [read: religious]- counterpublic [read: gendered] sphere of Orthodoxy.